Effect of Rapping Frequency and Intensity in Electrostatic Precipitator Efficiency - Banthoengjai, Thanpilin; Wiangtong, Theerayod; Pattanadech, Norasage; Pannil, Pittaya (My University, 2023)
Electrostatic precipitator (ESP) is one of air pollution control equipment which widely use in biomass power plant. There is a rapping system in ESP use for removing ash from collecting plate (CP) and discharge electrode (DE). Rapping frequency and intensity of rappers effect the efficiency of ESP because they relate to dust quantity in ESP. Dust layer at CP, which has $108\ \Omega\mathrm{m}$ of resistivity, can cause back corona. Back corona can cause spark in dust layer. To prevent back corona, ESP should operate at lower voltage. Therefore, ESP efficiency is also lower. A chance of ash accumulation is depended on ion charged in dust particle. Rapping cause re-entrainment of dust particle which is uncharged. Re-entrainment dust particle increase uncharged dust in charging area. Therefore, charging process require more ion to charge more dust particle but generating more ion can cause spark over in ESP. There is the appropriate rapping frequency and intensity of rapping due to ESP condition. To study the effect of rapping system in ESP, the experiment was set in 9 cases. The rapping system in the experiment was set as different round trip time (RTT), which determine the rapping frequency, and lifting distance, which determine the intensity. There are 3 different RTT, 2, 3, and 4 minutes, and 3 lifting distance, 8, 10, and 12 inches. Total suspended particulate (TSP) was measured by EPA Method 5 and analyzed by Isokinetic and Gravimetric method to compare the efficiency of ESP in each case. Changing in rapping frequency and intensity of rapping system affect TSP. In case which lifting distance is 8 and 10 inches, TSP tend to decrease when rapping frequency was decreased, means higher efficiency of ESP. On the other hand, TSP tend to increase when rapping frequency was decreased in case of lifting distance is 12 inches. The lowest TSP was the case with 4 minutes RTT and 8 inches lifting distance. From the experiment, there is an appropriate value of rapping frequency and intensity of rapping system. Setting rapping system improve ESP efficiency.
Keywords: electrostatic precipitator; lifting distance; rapping system; round trip time